Analisis Kebijakan PPDB dalam Perspektif Pemerataan Pendidikan, Isu Implementasi, dan Keterkaitannya dengan Pendidikan Karakter - Lalu Wirasantana; Winengan Winengan; Hadi Kusuma Ningrat (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze Indonesia’s student admission policy Penerimaan Peserta Didik Baru (PPDB) from the perspectives of educational equity, implementation issues, and its relationship with character education. The study employs a Systematic Literature Review (SLR) using literature from Scopus, Directory of Open Access Journals, and Google Scholar, limited to scholarly publications from the last ten years. The review was conducted through systematic identification, selection, and synthesis of relevant studies. The findings indicate that, conceptually, the zoning-based PPDB policy supports more equitable educational access, yet it has not fully ensured equality in educational quality. The major constraints lie in the interaction between unequal access, disparities in institutional quality, and weak verification mechanisms in online-based PPDB and achievement-based admission pathways. In addition, domicile data manipulation, academic dishonesty, and low integrity in selection processes suggest that character education has not been optimally internalized. This study highlights the need for PPDB reform that goes beyond administrative access and emphasizes educational quality, transparent governance, and stronger character values.